Research on compensation standards for cultivated land protection based on a value-added benefit model in Xinjiang, China - Wang, Yuejian; Yan, Xin; Wang, Lei; Xia, Baofei; Yang, Guang; Fan, Zili (Frontiers in Environmental Science, 2023)
This study examines the content of the compensation standard measurement for cultivated land protection to effectively address the imbalance between local economic development and cultivated land protection. The empirical analysis relies on a value-added benefit model. Using the grain supply and demand balance method, 14 prefectures (cities) in Xinjiang were divided into cultivated land deficit/surplus areas, and based on the theory of value-added benefits of converting cultivated land to construction land, a compensation standard measurement system for cultivated land protection was established, and correction coefficients such as potential urban development intensity and government payment capacity were introduced to accurately determine the realistic compensation standard for cultivated land protection in areas that are paid and receive compensation. The results of the study found that the total surplus area of cultivated land in Xinjiang is 271.57 × 104 hm2, which is in surplus overall, while within Xinjiang, four states (cities) are cultivated land deficit areas, which are also the areas that need to pay compensation amounts, and 10 states (cities) are cultivated land surplus areas, which receive compensation payments. The average compensation standard for cultivated land protection in Xinjiang is 24.27 × 104 RMB/hm2, while the compensation standard for cultivated land protection in each state (city) is mainly influenced by the benchmark land price and the comprehensive value of cultivated land, of which the benchmark land price is the core factor affecting the compensation standard. In terms of the total amount of compensation, the total amount of compensation paid for cultivated land protection in Xinjiang is 5,323.93 × 108 RMB, which is paid by the provinces where cultivated land is scarce, and in terms of the provinces, by the four compensation areas to the remaining 10 reimbursement areas, for which we put forward policy suggestions such as adopting diversified forms of compensation, alleviating financial pressure, financing through multiple channels, securing sources of funding, establishing cultivated land protection compensation standards, dynamic measurement platforms, and supervision and management mechanisms to realize long-term compensation mechanisms for cultivated land. The study is conducive to clarifying the rights and responsibilities of cultivated land protection, mobilizing the motivation of the main actors in cultivated land protection, and promoting balance and harmony between regional economic development and cultivated land protection.